Cinnamon roll murder [compact disc, unabridged] - Fluke, Joanne, 1943- (Fluke, Joanne, 1943- Hannah Swensen mystery., 2012)
The tour bus carrying the Cinnamon Roll Six overturns, sending the band members to the hospital--and the keyboard player to a bizarre and untimely death. Soon Hannah discovers the victim's surprising secret--and becomes determined to bring the killer to justice.